2010
DOI: 10.1002/cphc.201000301
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved ATR‐FTIRS Study of the Formation of Macroscopic Domains and Microislands during CO Electrooxidation on Pt

Abstract: Electrooxidation of CO in CO-saturated sulfuric acid electrolyte solutions with controlled mass transport is investigated with spatially resolved attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy under galvanostatic and potentiostatic conditions. The reaction conditions are chosen such that steady states with intermediate current densities and intermediate average CO coverages are accessible. We demonstrate that under these conditions the reaction never proceeds uniformly on the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 72 publications
0
22
0
1
Order By: Relevance
“…For example, surface heterogeneity is an important parameter in electrochemistry, particularly for polycrystalline electrodes, and may constitute the second degree of freedom necessary for complex oscillations to arise. In fact, it has been shown that even considerably simple reactions such as that for CO may display complex spatial distribution [63] and that electrochemical oscillatory reactions can possess a component in space [64]. Thus TFMSA could be acting on this parameter inhibiting specific sites by adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…For example, surface heterogeneity is an important parameter in electrochemistry, particularly for polycrystalline electrodes, and may constitute the second degree of freedom necessary for complex oscillations to arise. In fact, it has been shown that even considerably simple reactions such as that for CO may display complex spatial distribution [63] and that electrochemical oscillatory reactions can possess a component in space [64]. Thus TFMSA could be acting on this parameter inhibiting specific sites by adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…We employed spatially resolved attenuated total reflection (ATR) Fourier transform infrared (FTIR) spectroscopy 28 29 (also known as surface enhanced IR absorption spectroscopy, SEIRAS) to monitor the CO coverage in-situ in a flow cell as shown in Fig. 4 in the methods section below, where also experimental details are given.…”
Section: Resultsmentioning
confidence: 99%
“…[7] When stationary domains are formed, the S-NDR cannot be observed since the electrode potential value is nearly independent of the applied current and lies in the middle of the bistable region. [9,12,14] The observation of the S-NDR herein indicates that the diameter of the Pt microelectrodes is below the critical size required for pattern formation under the applied experimental conditions.…”
mentioning
confidence: 88%
“…Rather, when trying to adjust an intermediate current density, self-organized spatial patterns form spontaneously, such as CO-covered domains under galvanostatic control, [8,9] or Turing-type patterns under potentiostatic control and low electrolyte conductivity. [10,11,12] In the following, we show that the S-NDR current branch becomes accessible when the size of the electrode is sufficiently reduced, more precisely when the reaction proceeds on a single 9 mm diameter Pt microelectrode. Furthermore, coupling of several Pt microelectrodes leads to the emergence of new cooperative behaviour consisting of their sequential activation when the applied current is increased.…”
mentioning
confidence: 99%